Perancangan Tata Letak Fasilitas yang Ergonomis di Lingkungan Perkantoran - Renhard Sitohang; A. Harits Nu’Man; Nita P.A Hidayat (Bandung Conference Series: Industrial Engineering Science, 2022)
Abstract. Every organization needs an office as a place of concentration for leaders and employees to carry out their activities, to provide comfort while working, it is necessary to have a layout of facilities and a physical office environment that can provide comfort while working. The Rectorate Building of the Islamic University of Bandung is an office area and is used as a service center for university academic & administrative activities. The layout of the rooms in the Rectorate Building at this time has not considered the principle of office space arrangement. The physical environment of the office still needs to be evaluated to match the standard of the office physical environment, so that workers can feel comfortable while working. The research aims to evaluate the layout of the office, make a proposal for the design of the layout of the office space and the proposed improvement of the physical environment in the office space. The facility layout design uses ARC (Activity Relation Ship) which aims to determine the level of interaction between departments. The proposed layout uses the CORELAP (Computerized Relationship Layout Technique) algorithm. Standards for temperature, humidity, lighting, and noise are determined based on the Decree of the Minister of Health of the Republic of Indonesia No. 48. The redesign of the layout is done with the CORELAP Algorithm to produce a new layout by prioritizing parts/departments that have an absolute degree of closeness placed close together. The results of the analysis of physical environmental conditions of air temperature, humidity, lighting, and noise indicate that workers still feel comfortable to work at a temperature of 28 oC, so the addition of air conditioning does not need to be done. Air humidity can be reduced by making air vents and opening windows while working. The recommended lamp is a PHILIPS TL-D-54 lamp with a power of 30 Watts to match the lighting standards of the room. Noise levels of less than 85 dB can still be tolerated by workers without losing hearing. Temperature, humidity, lighting, and noise that are not in accordance with office space standards do not affect employee comfort while working because they can still be tolerated by workers. Abstrak. Setiap organisasi memerlukan kantor sebagai tempat konsentrasi pimpinan dan pegawai melakukan aktivitasnya, untuk memberi kenyamanan saat bekerja diperlukan tata letak fasilitas dan lingkungan fisik perkantoran yang dapat memberi kenyamanan saat bekerja. Gedung Rektorat Universitas Islam Bandung merupakan area perkantoran dan digunakan sebagai pusat layanan kegiatan akademik & administrasi universitas. Tata letak ruangan di Gedung Rektorat saat ini belum mempertimbangkan asas penataan ruang kantor. Lingkungan fisik kantor masih perlu dievaluasi agar sesuai dengan standar lingkungan fisik kantor, sehingga pekerja dapat nyaman saat bekerja. Penelitian bertujuan untuk mengevaluasi tata letak perkantoran, membuat usulan perancangan tata letak ruang kantor dan usulan perbaikan lingkungan fisik pada ruang kantor. Perancangan tata letak fasilitas menggunakan ARC (Activity Relation Ship) yang bertujuan untuk mengetahui tingkat interaksi antar departemen. Tata letak usulan menggunakan Algoritma CORELAP (Computerized Relationship Layout Technique). Standar suhu, kelembaban, pencahayaan, dan kebisingan ditentukan berdasarkan KEPMENKES RI No. 48. Perancangan ulang tata letak dilakukan dengan Algoritma CORELAP menghasilkan tata letak baru dengan mengutamakan bagian/departemen yang memiliki derajat kedekatan multak diletakkan berdekatan. Hasil analisis kondisi lingkungan fisik suhu udara, kelembaban, pencahayaan, dan kebisingan menunjukkan bahwa pekerja masih merasa nyaman untuk bekerja pada suhu 28 oC, sehingga penambahan AC tidak perlu dilakukan. Kelembaban udara dapat dikurangi dengan membuat ventilasi udara serta membuka jendela pada saat bekerja. Lampu yang direkomendasikan adalah lampu PHILIPS TL-D-54 dengan daya 30 Watt agar sesuai dengan standar pencahayaan ruangan. Tingkat kebisingan kurang dari 85 dB masih dapat ditoleransi pekerja tanpa menghilangkan daya dengar. Suhu, kelembaban, pencahayaan, dan kebisingan yang tidak sesuai dengan standar rungan kantor tidak mempengaruhi kenyamanan karyawan saat bekerja karena masih dapat ditoleransi oleh pekerja.